Ethnic and Sex Diversity in Academic Orthopaedic Surgery: A Cross-sectional Study. (8th March 2022) - Vij, Neeraj; Singleton, Ian; Bisht, Roy; Lucio, Francisco; Poon, Selina; Belthur, Mohan V.
Abstract : Introduction: Although the diversity in orthopaedic residency programs has been studied, the diversity within academic orthopaedics has not. Methods: The board of specialty societies, five leading journals and the National Institutes of Health RePORTER tool, and three accreditation organizations were explored. Results: The board of directors comprised 220 (72%) Caucasians, 36 (12%) Asians, 4 (1%) Hispanic/Latinos, 29 (9%) African Americans, and 18 (6%) Other individuals; 250 (81%) were men, and 57 (19%) were women. The editorial boards comprised 288 (77%) Caucasians, 62 (16%) Asians, 14 (4%) Hispanic/Latinos, 8 (2%) African Americans, and 4 (1%) Other individuals; 341 (91%) were men, and 35 (9%) were women. The National Institutes of Health grant recipients comprised 117 (64%) Caucasians, 58 (32%) Asians, 4 (2%) Hispanic/Latinos, and 3 (2%) African Americans; 128 (70%) were men, and 54 (30%) were women. On average, Caucasians, Asians, Hispanic/Latinos, and African Americans received 776, 543, 439, 600, 420, 182, and 494, 049, respectively. On average, men and women received 759, 426 and 419, 518, respectively. The accreditation boards comprised 45 (82%) Caucasians, 6 (11%) Asians, and 4 (7%) African Americans; 45 (82%) were men, and 10 (18%) were women. Conclusions: Academic orthopaedic surgery does not resemble the United States. Residency, fellowship committees, and professional organization boards need to become aware of these disparities.